Comparative Assessment of Heavy Metals in Soils of Designated Institutions in Rivers State, Nigeria - Edori, Onisogen Simeon; Iyama, William Azuka; Edori, Enize Simeon (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study was based on assessment of heavy metal levels in soils of designated Institutions in Rivers State, Nigeria. Ten (10) heavy metals of Cd, Pb, Cr, Ni, Fe, Cu, Ag, Zn, Co and As. The assessment was achieved through a pure experimental study design but adopted the probability cluster sampling technique. Heavy metal concentration analysis was done using the atomic absorption spectrophotometer (ASTMD 1971/4691). The ranges for Cd concentration in the soil in were; Uniport (0.54±0.06-0.63±0.01), IAUE (0.84±0.01-0.86±0.01) and RSU (0.72±0.01-0.75±0.01); Pb, Uniport (1.25±0.02-1.32±0.03), IAUE (1.00±0.06-1.15±0.05) and RSU (1.32±0.01-1.36±0.01); Cr, 0.33±0.01-0.37±0.01 (Uniport), 0.32±0.03-0.40 ±0.03 (IAUE) and 0.33±0.01-0.36±0.01 (RSU); Ni, 0.50±0.02-0.55±0.01 (Uniport), 0.32±0.03-0.40±0.01 (IAUE) and 1.56±0.01-1.60±0.01 (RSU); Fe, 150±2.88-156±1.41 (Uniport), 265±2.12-2.70±1.41 (IAUE) and 286±1.41-290±1.41 (RSU); Cu, 1.75±0.01-1.79±0.01 (Uniport), 1.54±0.04-1.62±0.02 (IAUE) and 1.56±0.01-1.60±0.01 (RSU); Ag, 0.74±0.02-0.80±0.02 (Uniport), 1.30±0.04-1.40±0.04 (IAUE) and 1.16±0.03-1.24±0.03 (RSU); Zn, 51.8±0.64-53.7±0.71 (Uniport), 53.4±0.14-53.8±0.14 (IAUE) and 46.0±0.14-46.4±0.14 (RSU); Co, 1.25±0.01-1.28±0.01 (Uniport), 1.30±0.04-1.40±0.04 (IAUE) and 1.45±0.02-1.50±0.01 (RSU); but As recorded a uniform concentration of < 0.002mg/kg in the three university campuses. There was low concentration of these heavy metals in the designated soils though gradually building up as the concentrations were below permissible limits (WHO, DPR-EGASPIN, NJDEP, MHSPE). Spatial variation for the three campuses using a one-way ANOVA showed no significant difference (p<0.05) as f-ratio was 0.08734 and p-value of 0.916654. Similarly, t-test was used to compare the mean values of two campuses Up/IAUE (t = -0.37829), Up/ RSU (t = -0.40194), IUAE/RSU (t = -0.03585). The greatest threats of soil heavy metal contamination due to future accumulation in the soils were found in Cd, Cr, Zn and Co. The potential variation of heavy metals in the study was of the trend, Fe>Zn>Ni>Cu>Co>Pb>Ag>Cd>Cr>As. There should be deliberate attempt to regulate unfriendly and harmful anthropogenic activities within the campuses especially sanitary habits.